Effects of moderately increased testosterone concentration on physical performance in young women: a double blind, randomised, placebo controlled study. Issue 10 (15th October 2019) - Hirschberg, Angelica Lindén; Elings Knutsson, Jona; Helge, Torbjörn; Godhe, Manne; Ekblom, Maria; Bermon, Stephane; Ekblom, Björn
Abstract : Objective: To investigate the effects of a moderate increase in serum testosterone on physical performance in young, physically active, healthy women. Methods: A double blind, randomised, placebo controlled trial was conducted between May 2017 and June 2018 (ClinicalTrials.gov ID: NCT03210558 ). 48 healthy, physically active women aged 18–35 years were randomised to 10 weeks of treatment with 10 mg of testosterone cream daily or placebo (1:1). All participants completed the study. The primary outcome measure was aerobic performance measured by running time to exhaustion (TTE). Secondary outcomes were anaerobic performance (Wingate test) and muscle strength (squat jump (SJ), counter movement jump (CMJ) and knee extension peak torque). Hormone levels were analysed and body composition assessed by dual energy X-ray absorptiometry. Results: Serum levels of testosterone increased from 0.9 (0.4) nmol/L to 4.3 (2.8) nmol/L in the testosterone supplemented group. TTE increased significantly by 21.17 s (8.5%) in the testosterone group compared with the placebo group (mean difference 15.5 s; P=0.045). Wingate average power, which increased by 15.2 W in the testosterone group compared with 3.2 W in the placebo group, was not significantly different between the groups (P=0.084). There were no significant changes in CMJ, SJ and knee extension. Mean change from baseline in total lean mass was 923 g for the testosterone group and 135 g for the placebo group (P=0.040). Mean change in lean mass in the lower limbs was 398 g and 91 g, respectively (P=0.041). Conclusion: The study supports a causal effect of testosterone in the increase in aerobic running time as well as lean mass in young, physically active women.